Revisiting Intentions at Hospital X's Medical Check-Up Service: A Review of Perceived Service Quality and Cost - Sutrisno, Sutrisno; Trimurtini , Indarti; Puspitasari , Kiki; Ayesha , Zahrah; Khoerunnisa , Nazwa; Pebryan , Allik (International Journal of Economics Development Research (IJEDR), 2024)
The purpose of this study is to obtain the results of a study of service quality, perceived price and revisit intentions at medical check-up services at X Hospital, as well as to obtain the results of an analysis of the related influence of service quality on revisit intentions at medical check-up services at X Hospital through perceived costs. Researchers conducted observations, interviews, and distributed questionnaires to 200 patients who had used medical check-up services. Path analysis was also used in this study. Medical check-up services at X Hospital are of high quality. However, the cost felt by patients when using medical check-up services is still felt to be less cheap. Even so, patients still have a desire to reuse the service because of the lack of choices available. Service quality is quite closely and significantly related to the perceived cost of medical check-up services. Similarly, service quality is quite closely and significantly related to the intention to revisit medical check-up services. This is not much different from the perceived cost which is quite closely and significantly related to the intention to revisit the medical check-up service. Regular customer service excellence training for all health workers can improve service quality, especially in this case, namely friendliness, speed and focus on the needs and desires of patients. The impact of this is an increase in patient satisfaction and desire to return to using medical check-up services at X Hospital. Furthermore, increasing the speed of service to patients (for example through optimisation of equipment and resources that have been owned) can increase satisfaction and desire to use medical check-up services. Furthermore, improving facilities and infrastructure (e.g. the technology used and the waiting room) can be done to increase people's desire to pay more for medical check-up services.